2018
DOI: 10.1103/physrevd.98.104023
|View full text |Cite
|
Sign up to set email alerts
|

Q curvature and gravity

Abstract: In this paper, we consider a family of n-dimensional, higher-curvature theories of gravity whose action is given by a series of dimensionally extended conformal invariants. The latter correspond to higher-order generalizations of the Branson Q-curvature, which is an important notion of conformal geometry that has been recently considered in physics in different contexts. The family of theories we study here includes special cases of conformal invariant theories in even dimensions. We study different aspects of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 81 publications
(78 reference statements)
0
12
0
Order By: Relevance
“…In the context of a top-down anisotropic deformation of a strongly coupled N = 4 Super-Yang-Mills (SYM) plasma driven by a nontrivial profile for a bulk axion field [128,129], the corresponding anisotropic drag forces [130][131][132], Langevin diffusion coefficients [133][134][135], and shear viscosities [136], have been already computed but a detailed holographic study of anisotropic momentum transport driven by an external magnetic field has not yet been done.…”
Section: Shear Viscosity 49mentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of a top-down anisotropic deformation of a strongly coupled N = 4 Super-Yang-Mills (SYM) plasma driven by a nontrivial profile for a bulk axion field [128,129], the corresponding anisotropic drag forces [130][131][132], Langevin diffusion coefficients [133][134][135], and shear viscosities [136], have been already computed but a detailed holographic study of anisotropic momentum transport driven by an external magnetic field has not yet been done.…”
Section: Shear Viscosity 49mentioning
confidence: 99%
“…In anisotropic environments, the approach used to obtain the drag forces was discussed in Refs. [130][131][132], while the Langevin coefficients were studied in Refs. [133][134][135].…”
Section: Appendix A: Revision Of Heavy Quark Momentum Transportmentioning
confidence: 99%
“…Subsequently, this idea has been generalized to various cases, such as chemical potential [18][19][20], finite coupling [21], non-commutativity plasma [22] and AdS/QCD models [23][24][25]. Other studies in this direction can be found in [26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…For this quantity in some AdS/QCD models, see [23][24][25]. Other important results can be found, for example, in [26][27][28][29][30][31][32][33]. Now we would like to give such analysis under the influence of a magnetic field.…”
Section: Introductionmentioning
confidence: 99%